Analyzing Professional Development Practices for Teachers in Public Universities of Pakistan - Aslam, Hassan Danial (Mediterranean Journal of Social Sciences, 2011)
Professional development for teachers is an essential element of plans to improve the quality of education.Professional development in a broader sense refers to the development of a person in his or her professional role. Morespecifically, professional development of teachers refers to the achievement of enhanced learning experience in research andteaching with synchronized system so that he/she could deliver effectual knowledge to his /her students in particular and to thesociety as a whole. Exploring this imperative aspect of teaching human resource in universities, current study analyzes theinitiatives taken by public universities of Pakistan for professional development of their teachers. The aim of this explanatorystudy is to investigate the issues and challenges regarding professional development mechanisms of public universities ofPakistan. It elaborates their performance development procedures and strategies and unearths the influential factors andchallenges which are faced by these university teachers regarding performance development systems. The sample of the saidstudy comprised of randomly selected teaching staff of five major Public Universities of Pakistan. Along with detailquestionnaires, in depth interviews had been conducted with teaching staff of the sample universities in order to achieve thedeeper insights of the challenges and issues regarding teachers’ professional development. The study reveals that foreignscholarships to university teachers, research grants and training programs are various effectual measures taken by HigherEducation Commission of Pakistan for Public universities. However, comprehensive monitoring system, quality assurance andimpact measurement of the said measures are lacking elements which create dissatisfaction among teachers in publicuniversities of Pakistan. Also, lack of training for improved teaching in semester system, communication gap among seniors andjunior faculty, decreased guidance for modernized research conduction, overburdened teaching load are some of the hinderingfactors in professional development of teachers which are been revealed by the current research.